Modeling, dynamics, optimization and bioeconomics III : DGS IV, Madrid, Spain, June 2016, and Bioeconomy VIII, Berkeley, USA, April 2015 - selected contributions /: DGS IV, Madrid, Spain, June 2016, and Bioeconomy VIII, Berkeley, USA, April 2015 - selected contributions. (2018) - Unknown
No abstract available